Intravascular catheter related infections in children admitted on the paediatric wards of Mulago hospital, Uganda - Nahirya, Patricia (Makerere Medical School, 2008)
INTRODUCTION: Worldwide use of intravascular catheters (IVC) has been associated with both local and systemic infections. No studies have been done in the sub-Saharan region on IVC related infections. OBJECTIVE: To determine the prevalence, causative organisms and their antimicrobial susceptibility pattern and the factors associated with infections related to short term peripheral venous catheters in children admitted to the general paediatric wards in Mulago Hospital, Uganda. METHODS: A cross-sectional study of 391 children aged one day to 12 years, on Jelliffe ward in Mulago Hospital, who had short peripheral venous intravascular catheters uncoated with no antibiotic or antiseptic, was done. Social demographic characteristics, anthropometry, clinical examination including the catheter site were determined at enrollment. The children had their blood, catheter tip and hub samples taken off for culture and sensitivity as well as complete blood counts. The data collected was entered using EPI-INFO and analysed with SPSS packages. RESULTS: Out of the 391 short term peripheral venous catheters collected, 20.7% catheter tips and 11.3% catheter hubs were colonised. Phlebitis was observed in 17.4%. Bacteria isolated from colonised catheter tips were Staphylococcus aureus (60.5%), Staphylococcus epidermidis (23.5%). The most common organism isolated from the hub was Staphylococcus aureus (56.8%) followed by Staphylococcus epidermidis (18.1%). Gram positive and negative organisms were sensitive to ciprofloxacin, gentamycin for gram-negative organisms and augmentin, cefuroxime, ceftriaxone for the gram-positive organisms. After logistic regression, factors such oedema, modified Glasgow coma score of <10/15, 6 hourly benzyl penicillin were significantly associated with colonisation of the tip while use of 25% dextrose, chloramphenicol 6 hourly and blood transfusion were significantly associated with colonisation of the hub. CONCLUSION: The study showed that infections related to short peripheral venous catheters in paediatric general wards in Mulago Hospital occurs and prevalence was 20.72% for tips and 11.3% for hubs.